Environmental Knowledge and Assessment Tool - Erickson, Larry E. (Kansas State University, 2010)
One Health refers to the interconnected nature of the health and well-being of people, animals and the environments that they share. Central to this idea, is the realization that adverse health-effects in one area are linked to adverse effects in other area. Therefore, sustainable human health is intimately linked with sustainable animal and environmental health. This panel will include discussions of important and emerging aspects of One Health by experts in this field, each with specializations in different, but complementary, aspects of One Health that covers a wide range of disciplines and areas of expertise.
Keywords: Environment; Assessment; Software; Air emissions; Environmental impact